Overexpression of Long Non-Coding RNA Linc01315 Predicts Poor Prognosis in Breast Cancer - Xue, Jingyan; Huang, Sheng; Chen, Jiaying; Chen, Yi-zuo; Shao, Zhi-min; Wu, Jiong; Chi, Yayun (Frontiers in Oncology, 2021)
Background LncRNAs have been shown to play critical roles in regulating tumorigenesis and tumor progression. Using LncRNAs to predict prognosis and therapeutic response to cancer treatment has been caused for concern, but the predictive value of lncRNAs remains to be explored and underlying mechanisms have not been completely understood. Methods The Linc01315 expression level was detected in 282 breast cancer tissues by using quantitative RT-PCR. The association between Linc01315 expression level and clinicopathological features of these breast cancer patients was further analyzed. Multiple regression analysis was used to evaluate Linc01315 predictive value of patients’ prognosis. Results Our study revealed that Linc01315 expression level was significantly correlated with vessel invasion (P = 0.028) and tumor subtype (P = 0.039). The Kaplan–Meier survival curves demonstrated that patients with lower Linc01315 expression level had significantly longer disease free survival (DFS) (P = 0.002) and overall survival (OS) (P=0.019). Multiple regression analysis showed that Linc01315 level could be an independent predictive factor for DFS (hazards ratio = 0.613, 95% confidence interval = 0.375-1.003; P = 0.049) and OS (hazards ratio = 0.439, 95% confidence interval = 0.228-0.845; P = 0.014). Further analysis showed that low Linc01315 level patients with endocrine therapy could benefit patients DFS (P=0.037) and OS (P=0.025). Conclusion Our results demonstrate that Linc01315 expression level is significantly correlated with breast cancer patients’ prognosis. Linc01315 may represent an independent prognostic marker and therapeutic target in breast cancer.